2023
DOI: 10.1007/s40820-023-01069-7
|View full text |Cite
|
Sign up to set email alerts
|

Progression in the Oxidation Stability of MXenes

Abstract: MXenes are under the spotlight due to their versatile physicochemical characteristics. Since their discovery in 2011, significant advancements have been achieved in their synthesis and application sectors. However, the spontaneous oxidation of MXenes, which is critical to its processing and product lifespan, has gotten less attention due to its chemical complexity and poorly understood oxidation mechanism. This perspective focuses on the oxidation stability of MXenes and addresses the most recent advancements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(46 citation statements)
references
References 60 publications
0
45
0
1
Order By: Relevance
“…84,88 Several strategies can be deployed for improving the intrinsic stability of MXenes, including improvement of the synthesis protocols, enhancement of the MAX phase quality, optimization of the atomic defects, employment of efficient stabilization tactics providing regulated surface moieties, and investigation of the correlations between the properties and the flake size. 89…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…84,88 Several strategies can be deployed for improving the intrinsic stability of MXenes, including improvement of the synthesis protocols, enhancement of the MAX phase quality, optimization of the atomic defects, employment of efficient stabilization tactics providing regulated surface moieties, and investigation of the correlations between the properties and the flake size. 89…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…84,88 Several strategies can be deployed for improving the intrinsic stability of MXenes, including improvement of the synthesis protocols, enhancement of the MAX phase quality, optimization of the atomic defects, employment of efficient stabilization tactics providing regulated surface moieties, and investigation of the correlations between the properties and the flake size. 89 Several reviews have comprehensively addressed the topic of MXenes production. [90][91][92] These 2D materials are typically fabricated by etching approaches, including molten-salt, HF-free, and electrochemical etching.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…As the oxidation of Ti 3 C 2 T x MXene proceeds, the edge-formed TiO 2 particles grow throughout the layered structure, resulting in a proportional reduction in the concentration of MXene-flakes and their size . Based on the recent reports on overcoming this issue, , the major strategies that can be employed to enhance the oxidation stability can be listed as follows. Careful selection of the MAX phase precursors. Since MXenes are topo chemically produced from their parent MAX phases, the MAX phase’s quality has a significant impact on the MXene structure and characteristics …”
Section: Synthesis and Processing Of Ti3c2t X Mxenementioning
confidence: 99%
“…However, a method to halt the spontaneous aqueous oxidation of MXenes should be proposed before MXenes can be applied to batteries. 14 Single-layered MoS 2 is a promising anode material for SIBs and PIBs due to the isotropic ion transport paths and high specific capacity. Zhang et al 15 found that MoS 2 @C and Fe 7 S 8 @C in dimethyl ether (DME) electrolyte have promising potential for fast SIBs and PIBs with a higher initial coulombic efficiency and capacity when compared with those in ethylene carbonate/diethyl carbonate electrolyte.…”
Section: Introductionmentioning
confidence: 99%